1995
DOI: 10.1128/mcb.15.3.1210
|View full text |Cite
|
Sign up to set email alerts
|

Novel CDC34 (UBC3) ubiquitin-conjugating enzyme mutants obtained by charge-to-alanine scanning mutagenesis

Abstract: CDC34 (UBC3) encodes a ubiquitin-conjugating (E2) enzyme required for transition from the G 1 phase to the S phase of the budding yeast cell cycle. CDC34 consists of a 170-residue catalytic N-terminal domain onto which is appended an acidic C-terminal domain. A portable determinant of cell cycle function resides in the C-terminal domain, but determinants for specific function must reside in the N-terminal domain as well. We have explored the utility of ''charge-to-alanine'' scanning mutagenesis to identify nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 52 publications
5
28
0
Order By: Relevance
“…In E2 enzymes, the core Ubc domain appears to be sufficient for their enzymatic activity, while the extensions at either end could serve as modules for protein-protein interactions that direct the enzyme to specific substrates or subcellular locations (2,20,27,38,48). The unique amino termini of the different isoforms of HsUEV-1 might be involved in specific protein-protein interactions which may affect their localization or activity.…”
Section: Discussionmentioning
confidence: 99%
“…In E2 enzymes, the core Ubc domain appears to be sufficient for their enzymatic activity, while the extensions at either end could serve as modules for protein-protein interactions that direct the enzyme to specific substrates or subcellular locations (2,20,27,38,48). The unique amino termini of the different isoforms of HsUEV-1 might be involved in specific protein-protein interactions which may affect their localization or activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, conserved ScCdc34 S97 (S95 in human Cdc34) is essential for cell viability (14) and is required for supporting E2 monomer interactions or polyubiquitin chain assembly on the E2 protein (32). Other critical ScCdc34 sites include a conserved acidic insertion loop (residues 103 to 114 [residues 102 to 113 in humans]) (14,23) and the charged cluster (residues D144, D148, R150, K151, and E154 [residues D143, R149, K150, and E153 in humans]) (23).…”
mentioning
confidence: 99%
“…To identify the functional domain of Cdc34 that is essential for acquisition of resistance to MeHg, we constructed several Cdc34 mutants 4,5) that had no ubiquitin-conjugating activity and examined their MeHg sensitivity, thereafter. Our results showed that the MeHg sensitivity of yeast cells that overexpressed Cdc34 mutants did not significantly differ from that of the control yeast cells.…”
Section: Reduction In Mehg Toxicity By Up System-mediated Acceleratiomentioning
confidence: 99%